Antioxidant Activity Test from Vegetable Tomato (Solanum lycopersicum) and Cherry Tomato (Solanum lycopersicum var. Cerasiforme) in Hand and Body Cream - Farida Nuraeni; Leny Heliawati; Melani Nurastuti (Helium: Journal of Science and Applied Chemistry, 2022)
Dry, scaly, rough skin conditions accompanied by wrinkles and black spots characterize the skin that experiences premature aging. One of the causes of premature aging is free radicals. These free radicals can be overcome with natural or artificial antioxidants. Natural antioxidants are found in fruits and vegetables, one of which is tomatoes. Tomatoes in direct use are less effective, so they are made in the form of hand and body cream. Production of vegetable tomato and cherry tomato extracts fruit extraction and maceration using 96% ethanol, then concentrated with a rotary evaporator until the extract is thick. The extracts of vegetable tomatoes and cherry tomatoes were then tested for phytochemical, antioxidant activity, and identification of compounds with LC-MS, then applied to hand and body cream with a concentration of 1% and 3% with codes F0, F1, F2, F3, and F4. Hand and body cream of tomato extract are tested by measuring pH, viscosity, specific gravity, total microbial Contamination, homogeneity and testing for antioxidant activity using the DPPH method. Phytochemical test results showed that flavonoid compounds were present in both extracts. The antioxidant activity of vegetable tomato ethanol extract was obtained with an IC50 value of 947.81ppm, and an IC50 value of 473.51 ppm was obtained for cherry tomato extract. From the LC-MS analysis, the compounds contained in cherry tomatoes, namely esculeoside A and B as cytotoxic activity, dehydrotomat as an antibacterial, kaempferol-3-O-rutinoside as an antioxidant, and tomatidine as an antibiotic. Antioxidant activity of hand and body cream, hand and body cream F4 (964.05 ppm), hand and body cream F3 (1001.97 ppm), hand and body cream F2 (1033.73 ppm), hand body cream F1 (1036.61 ppm), and hand and body cream F0 (1486.14 ppm). Hand and body cream cherry tomato extract 3%, formula 4 (F4), has the highest antioxidant activity. It can be concluded that the addition of extract concentration affects the antioxidant activity value of hand and body cream. Body cream F2 (1033.73 ppm), hand body cream F1 (1036.61 ppm), and hand and body cream F0 (1486.14 ppm). Hand and body cream cherry tomato extract 3%, formula 4 (F4), has the highest antioxidant activity. It can be concluded that the addition of extract concentration affects the antioxidant activity value of hand and body cream. Body cream F2 (1033.73 ppm), hand body cream F1 (1036.61 ppm), and hand and body cream F0 (1486.14 ppm). Hand and body cream cherry tomato extract 3%, formula 4 (F4), has the highest antioxidant activity. It can be concluded that the addition of extract concentration affects the antioxidant activity value of hand and body cream.